Prediction of Network Threats and Attacks by Mathematical Simulation - Daniil Doroshenko (Challenges and Issues of Modern Science)
Purpose. The purpose of the article is a comprehensive study of modern methods of mathematical modeling of network threats and attacks, as well as studying their effectiveness. Design / Method / Approach. The research uses mathematical methods such as probability theory, game theory, graph models, and statistical approaches to build models that allow to reproduce the dynamics of threats in real networks. The methodology is based on modeling various attack scenarios, affecting information security. Findings. The study showed that mathematical models do not allow analyzing complex network processes, predicting the emergence of new threats and identifying vulnerabilities in networks. Using these models makes it possible to create precise algorithms to prevent attacks, which in turn achieve the reliability and security of the network infrastructure. Theoretical Implications. The research contributes to the development of theoretical knowledge about the application of mathematical methods in cyber security, especially in the conditions of the constant expansion of network threats. The models presented in the work offer new ways of assessing risks and analyzing attacks. Practical Implications. The proposed approaches can be used by network administrators and cyber security specialists to develop effective strategies for protecting information systems. Mathematical modeling allows not only to analyze existing threats, but also to predict the emergence of new ones. Originality / Value. The article is distinguished by its originality due to the integration of various mathematical approaches in the study of network threats. This research provides a unique opportunity to gain a deeper understanding of the nature of cyberattacks, making it a valuable resource for security professionals. Research Limitations / Future Research. The study has a limitation related to the fact that the presented models apply only to certain types of network threats. In future research, it is advisable to extend these models for other forms of attacks and explore the possibilities of their integration into different systems. Article type. Review of Methods.